Analysis and development of a cutting force measurement system under pre-heating conditions of the workpiece - Pasternak, Serhiy; Stupnytskyy, Vadym (Видавництво Львівської політехніки, 2024)
The issue of determining cutting forces in machining processes is relevant due to the need to improve the efficiency, quality, and accuracy of hard-to-machine materials. In particular, preventive heating of the workpiece can reduce the mechanical resistance of the machined material, which reduces the load on the tool and increases its service life. The article aims to study and analyze the equipment design for measuring cutting forces under conditions of preventive heating. The article discusses the key features of various types of dynamometers, including piezoelectric, strain gauge, mechanical, and hydraulic, which are used to record force effects while processing multiple materials. The advantages and limitations of each dynamometer type are presented, considering specific operating conditions, including temperature, possible deformations, and resistance to mechanical stress. The design features of equipment for studying cutting forces under conditions of preventive heating are described. The article also focuses on the measurement range, a critical parameter when working with different materials. The choice of metrology equipment depends on the workpiece’s material, the processing temperature regime, and accuracy requirements. Correct equipment setup and calibration ensure high accuracy and stability of measurements even in difficult conditions, such as preventive heating.
Keywords: cutting force; preheating; strain gauge; dynamometer; thermal strain; stress; cutting load